Study of light-matter interaction in single-layer molybdenum disulfide coupled to gold structures - Lemes, Matheus Fernandes Sousa (2023)
This dissertation studies the light-matter interactions in MoS2 monolayers deposited over gold gratings. We aim to characterize this hybrid devices morphological, vibrational, and optical properties. Our investigation started with the characterization of the semiconductor film morphology in different sample regions. We observed large height deformations for the MoS2 monolayer in the gratings, along with various defects. Then, Raman spectroscopy was used to study the vibrational properties of the two most pronounced Raman modes of MoS2, namely the E and A 1 modes. Raman hyperspectral maps showed that the peak positions of those modes are susceptible to the underlying spatial distribution. In particular, by constructing a correlative plot of the A 1 vs. E peak frequencies, we could evaluate the contributions of strain, doping, and plasmonic effects on the frequency changes of those modes. Interestingly, we observed that the electron concentration on the gold gratings depends on the polarization of the incident radiation, which was attributed to a plasmon-induced hot electron injection. Finally, the emission of exciton and trion states was investigated using photoluminescence (PL) spectroscopy. Partial PL quenching of the MoS2 over the gold substrate reveals the existence of charge transfer from the semiconductor to the metal. However, the charge transfer is not particularly efficient, probably due to air and water contaminations between the film and substrate that prevents good direct contact. We also observed a polarization-dependent trion to A exciton ratio, which further corroborated the existence of a plasmon-induced doping mechanism. These findings may help elucidate some underlying physics in hybrid MoS2/Au nanostructures, which can benefit fundamental studies and technological applications.